Control químico de trips Frankliniella occidentalis Pergande, 1895 en cultivo de sandía Citrullus lanatus Thunb, 1916 - Montoya Bravo, Kevin Adrián (2022)
The western thrips F. occidentalis is found on a wide host range, including numerous horticultural and ornamental greenhouse plants and various weeds. It is a specifically essential pest of watermelon, cucumber, bell pepper, eggplant and many ornamentals. Direct damage is due to feeding bites and laying effects. Feeding by adults and nymphs causes discoloration of affected tissue. Initially silvery and later brown plaques of variable length and abnormal but well-defined outline are found. The presence in these spots of small dark, inexpressive dots similar to deposits of fecal fluid allows them to be differentiated from those resulting from mites. When the bites occur in young tissues or growing organs, they cause deformations or distortions, and in floral organs they cause abortion or desiccation and fall. The information obtained was carried out through the technique of analysis, synthesis and summary, with the purpose of informing the reader about the chemical control for the management of thrips Frankliniella occidentalis Pergande, 1895 in watermelon crop Citrullus lanatus Thunb, 1916. From the above, it was determined that direct damage is due to the feeding of nymphs and adults, particularly on the lower part of the leaves, leaving a silvery appearance on the affected organs, which then appear necrotic. Indirect damage is the greatest and is due to the transmission of Tomato noticed wilt virus (TSWV), which affects watermelon, bell pepper, tomato, eggplant and bean. The mixture of two insecticides Spinetoram + Pyriproxyfen for the control of F. occidentalis showed quality results on the second and third days of application, reducing the population by 74 and 53%, respectively. A good result was obtained with the active ingredient Thiacloprid with a mortality of 26 thrips per plant.